Diana Agrest Mario Gandelsonas : On practice (A+U)
Se compilan obras, proyectos y textos críticos sobre y del estudio. Contiene: Intrductory Essays : On Practice - 1979. Architecture as A Cultural Practice - 1977. Not Architecture but Architecture (some fragments) : Set of Stores for Pierre Cardin, Buenos Aires 1970.Les Echelles : House for a Musician in Majorca, Spain 1975. Preliminary Sketches for a Building that Classifies Human Bodies According to Physical and Psychological Characteristics and Stands as a Monument to the Progrssive Nature of Secular Modern Architecture 1968-1975. Design as Reading : Housing Project for Roosevelt Island, N.Y. 1975. Transformation and Articulation of Types : Housing Proposal in Paris for the French Ministere of Housing 1975. Architecture as Mise en Sequence : Project for The International Competition for The Renewal of The Area of La Villette Paris : Second Prize / 1976. Architecture Between Memory and Amnesia : Proposal for A Suburban Center in Minneapolis on The Edge of The Mississippi River 1976. Three Variations on a Theme : Three Urban Buildings (Under Construction) 1977. On the Notion of Door : A Summer House 1977.